Barriers to innovation: the case of Ghana and implications for developing countries - Frank L. Bartels; Ritin Koria; Elisa Vitali (Triple Helix, 2016)
This paper analyses the barriers to innovation and innovativeness in the Ghana National System of Innovation (GNSI) in terms of the quadrilateral relationships between the following four actors: (a) government; (b) medium- and high-technology industries; (c) knowledge-based institutions; and (d) arbitrageurs (venture capital, finance capital and knowledge brokers). The paper contributes to research on systems of innovation in view of the wide recognition of the importance of National System of Innovation (NSI) for economic performance. The barriers to innovation in Ghana identified, through factor analysis, provide a framework to isolate systemic problems and enable policy makers to enhance effective policy delivery at the system level. This empowers the four actors to overcome the specific barriers to innovation and thus enabling the overall GNSI, through increased effectiveness and efficiency, to achieve higher levels of competitiveness. We find that barriers to innovation and innovativeness in Ghana factor significantly into the following: skills-Information and Communication Technology (ICT) capability/capacity; unsophisticated markets; deficient fiscal policy; and organisational risks.
Keywords: 330; Innovation policy; Innovation; National Systems of Innovation; Quadruple helix